2013
DOI: 10.1523/jneurosci.4078-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Encoding and Retrieval of Artificial Visuoauditory Memory Traces in the Auditory Cortex Requires the Entorhinal Cortex

Abstract: Damage to the medial temporal lobe impairs the encoding of new memories and the retrieval of memories acquired immediately before the damage in human. In this study, we demonstrated that artificial visuoauditory memory traces can be established in the rat auditory cortex and that their encoding and retrieval depend on the entorhinal cortex of the medial temporal lobe in the rat. We trained rats to associate a visual stimulus with electrical stimulation of the auditory cortex using a classical conditioning prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(57 citation statements)
references
References 57 publications
4
50
0
Order By: Relevance
“…However, a recent study by Chen et al (2013) demonstrated that the neocortex is involved in the process of information storage from the beginning of memory encoding. Therefore, combining these results with the results of our current experiment, we propose a new model in which a new memory is encoded in both the neocortex and the hippocampus that are associated via the EC.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, a recent study by Chen et al (2013) demonstrated that the neocortex is involved in the process of information storage from the beginning of memory encoding. Therefore, combining these results with the results of our current experiment, we propose a new model in which a new memory is encoded in both the neocortex and the hippocampus that are associated via the EC.…”
Section: Discussionmentioning
confidence: 99%
“…The parameters of the paradigm were set based on a previous research (Chen et al, 2013). A combined stimulus of a 100-ms light and a 20-ms sound (200-ms delay from the onset of the light) was used as the conditioned stimulus (CS) and a 500-ms foot shock (500-ms delay from the onset of the light) was used as the unconditioned stimulus (US), as illustrated in Fig.…”
Section: Fear Conditioning Trainingmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition these primary sensory areas, posterior and prefrontal association cortices also play a role in representing cross-modal associations (Fuster et al, 2000). The arbitrary associations are believed to be initially mediated via medial temporal cortex connecting the unimodal sensory cortices (McClelland et al, 1995; Miyashita et al, 1996, 1998; Frankland and Bontempi, 2005; Eichenbaum et al, 2007; Chen et al, 2013). Over time, these medial temporally mediated memory traces become independent of medial temporal structures and dependent upon posterior and prefrontal association cortices (Frankland and Bontempi, 2005).…”
Section: Introductionmentioning
confidence: 99%